The Effect of Content Marketing on Customer Advocacy with Brand Trust and Customer Engagement as Intervening Variables in the TikTok Application in Medan City - Handayani, Erma Florentina; Ginting, Paham; Lubis, Arlina Nurbaity (East Asian Journal of Multidisciplinary Research, 2024)
This research adopts a quantitative method approach. Primary and secondary data are obtained through documentation studies and online questionnaire collection using the Likert scale. The population for this study comprises all TikTok application users in the city of Medan. Path analysis is used to analyze the data in this research. The results indicate that content marketing positively and significantly affects brand trust. Content marketing also has a positive and significant direct effect on customer engagement. Brand trust has a positive and significant direct effect on customer advocacy. Customer engagement has a positive and significant effect on customer advocacy. The research also reveals that content marketing indirectly has a positive and significant effect on customer advocacy through brand trust, and content marketing has a positive and significant effect on customer advocacy through customer engagement as an intervening variable.